Auditing public broadcasting performance - Brants, Kees (Javnost (Ljubljana), 2003)
In most West European countries public service broadcasting (PSB) is in a state of flux, if not in crisis. Across the board, organisations are loosing their audience, particularly among the younger viewers, they are confronted with a critical and sometimes hostile political environment, and the self-evidence of their financial support or even their raison d'etre is put into question, not least by their competitors. In short: they are often fighting for support and struggling to survive. What's been going on here in the last ten, twenty years that merits such lamentation and is prompting a discussion about its mission and responsibilities? Do PSBs still deserve theirpreferential treatment in the broadcasting market, what responsibilities does that then entail, and how are they held to account for their "public" performance? A short overview is an introduction to a special issue on the theoretical grounding of, and empirical experiences with, auditing public broadcasting performance.
Keywords: mass media; množični mediji; radio; television; televizija; kvaliteta; informiranje; obveščanje; democracy; demokracija; svoboda; objektivnost; javnost